Hubungan Durasi Penggunaan Gawai dan Blue Light Filter dengan Tension-Type Headache (TTH) pada Mahasiswa Rumpun Teknik Fakultas Sains dan Teknik Universitas Nusa Cendana - Kenyndra Obrient Christ Adi Utama; Herman Pieter Louis Wungouw; Christina Olly Lada; Audrey Gracelia Riwu (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Tension-type headache (TTH) has a high prevalence among university students, a population characterized by intensive digital device use. This study aimed to explore the contribution of device usage duration and blue light filter implementation to the risk of developing TTH. To analyze the association between digital device usage duration and blue light filter utilization with the incidence of TTH among engineering students at the Faculty of Science and Engineering, Universitas Nusa Cendana. This study employed a quantitative correlational design with a cross-sectional approach. Participants were recruited using consecutive sampling, involving 68 students. TTH was identified using the Headache Screening Questionnaire (HSQ), while data on device usage duration and blue light filter utilization were collected through a structured questionnaire. Bivariate analysis was conducted using the Chi-Square test, followed by contingency coefficient calculation to determine the strength of association. A statistically significant association was found between digital device usage duration and TTH incidence (p < 0,05), with a moderate correlation strength. Conversely, no significant association was observed between blue light filter utilization and TTH incidence (p > 0,05). Digital device usage duration constitutes a significant risk factor for TTH among engineering students, whereas blue light filter utilization did not demonstrate a meaningful protective effect.